Excision Repair Cross Complementation Group 1 Single Nucleotide Polymorphisms and Nivolumab in Advanced Non-Small Cell Lung Cancer - Aiello, Marco Maria; Solinas, Cinzia; Santoni, Matteo; Battelli, Nicola; Restuccia, Nunzio; Latteri, Fiorenza; Paratore, Sabrina; Verderame, Francesco; Albanese, Giuseppina Valeria; Bruzzi, Paolo; Soto Parra, Hector Josè (Frontiers in Oncology, 2020)
Background: We hypothesized that non-small cell lung cancer (NSCLC) patients with a tumor positive for single nucleotide polymorphisms (SNPs) of the Excision Repair Cross Complementation Group 1 (ERCC-1) gene could be more genetically instable and consequently more responsive to a programmed cell death-1 (PD-1) blockade. Methods: We evaluated the T19007C and C8092A ERCC-1 SNPs by pyrosequencing assay, on tumor specimens from two independent cohorts of patients who relapsed after one or more prior systemic treatments for advanced NSCLC and who received nivolumab (3 mg/kg intravenously every 2 weeks) as part of the Italian Expanded Access Program. We aimed to assess the outcome of enrolled subjects according to the ERCC-1 SNPs status, to evaluate the role of these polymorphisms as putative biomarkers associated with a response/clinical benefit to anti-PD-1 therapies. Results: Of the 45 patients included in the final analysis, 21 (47%) and 16 (36%) were positive for the T19007C and C8092A polymorphic genotype (PG), respectively. In univariate analyses, overall survival (OS) and progression free survival (PFS) were shorter in patients with the T19007C PG, but neither difference achieved statistical significance (P = 0.131 and P = 0.717, respectively). The presence of the C8092A PG was associated with a longer OS and PFS, although statistical significance was only reached for PFS (P = 0.112 and P = 0.025, respectively). These results were confirmed by multivariate analyses. The response rate was only significantly higher in patients with the C8092A PG vs. wild type ERCC-1 (62 vs. 7%, P < 0.001). Conclusions: Results from this hypothesis generating pilot study, provided suggestive evidence that a subgroup of NSCLC patients could benefit differently from nivolumab according to the C8092A ERCC-1 SNP status. However, these data warrant further investigation.